A new path from welfare to work: The new welfare and the potential for workforce development - Oren M. Levin-Waldman (Levy Economics Institute of Bard College, 1997)
The author of this brief asks why welfare, workforce development, and unemployment insurance are operated as separate entities. If the goal of the new welfare law is to end dependency and foster a work ethic, then it needs to be tied more closely to existing policy aimed at developing the workforce. Instead of viewing the new welfare system as welfare policy with a new flexibility, we should see it as an opportunity to create a more comprehensive and coherent employment program to replace outmoded public assistance.
Keywords: 330